Romance „Les Adieux” Teodora Leszetyckiego – pożegnanie z Petersburgiem - Nidecka, Ewa (Wydawnictwo Uniwersytetu Rzeszowskiego, 2024)
Romance "Les Adieux" by Theodor Leschetizky was written around 1890. The piece is associated with Petersburg, where in the years 1858–1878 he gave piano lessons at the local conservatory. The composer dedicated the piece to Princess Tatiana Alexandrovna Yusupova, daughter of a Russian diplomat of Swiss origin, count Alexander Ivanovich Ribeaupierre. The composition belongs to the circle of salon music that characterizes many works composed in the 19th century. It refers to the waltz genre, numerous examples of which can be found in the works of P. Tchaikovsky. Melodiousness, smooth harmony, calm musical narrative, these are the main features of the piece. The composer used also numerous harmonic changes, figurations and varied articulation, which give the whole piece lightness. He does not use a single cantilena pattern, but based on the main motivic model, introduces various melodic variants through repetitions, which increases the sound value of the miniature.
Romance "Les Adieux" by Theodor Leschetizky – Farewell to Petersburg
Keywords: Theodor Leschetizky; Romaticism; piano miniature; Romance; Petersburg